A CONTRIBUTION TO KNOWLEDGE OF THE BALKAN LEPIDOPTERA. SOME PYRALOIDEA (LEPIDOPTERA: CRAMBIDAE & PYRALIDAE) ENCOUNTERED RECENTLY IN SOUTHERN SERBIA, MONTENEGRO, THE REPUBLIC OF MACEDONIA AND ALBANIA - Plant, Colin W.; Beshkov, Stoyan; Jakšić, Predrag; Nahirnić, Ana (Bulletin of Natural Sciences Research, 2017)
Pyraloidea (Lepidoptera: Crambidae & Pyralidae) were sampled in the territories of southern Serbia, Montenegro, the Former Yugoslav Republic of Macedonia and Albania on a total of 53 occasions during 2014, 2016 and 2017. A total of 173 species is reported here, comprising 97 Crambidae and 76 Pyralidae. Based upon published data, 29 species appear to be new to the fauna of Serbia, 5 species are new to the fauna of Macedonia and 37 are new to the fauna of Albania. The data are discussed.